Mathematic Communication Ability Achievement and Mathematical Habits of Mind Through Numbered Heads Together With Written Corrective Feedback - ALISYAH, SITI NUR; Katono, Kartono; Asih, Tri Sri Noor (Universitas Negeri Semarang, 2021)
This research describes mathematics communication through Numbered Heads Together (NHT) with written corrective feedback based on the students' levels of mathematical habits of mind and the correlation between written and spoken mathematics communication ability. This research is a mixed method with sequential explanatory design. It is a combined design between quantitative and qualitative. The population consisted of seventh graders of Rembang 4 Junior High School. The findings showed that NHT with written corrective feedback was effective for mathematics communication ability and mathematical habits of mind. The description results of mathematics communication ability are based on different levels of mathematical habits of mind (MHoM). From three students with high, moderate, and low mathematics communication ability, they had scores of 1, 2, and 0. On the fifteen moderate MHoM students, those with high, moderate, and low mathematics communication ability had scores of 1, 14, and 0. On four low MHoM students, those with high, moderate, and low mathematics communication ability obtained scores of 1, 3, and 0.